PENERAPAN PEMBELAJARAN MODEL EXPERIENTIAL KOLB UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KOMPETENSI MEMAHAMI DASAR - DASAR MESIN - Laksana, Nur Akhlis Sarihidaya (Journal of Mechanical Engineering Learning, 2014)
In the observation made ââin SMK Negeri 1 Ampelgading Pemalang , teachers still use the learning model on conventional model of learning that occurs in one direction , so the learning process ari teachers only. Issues raised in the study is that there is a difference or not between the use of Kolbs experiential learning model and conventional learning on competency models to understand the basics of the machine ? The goal is to prove judging or not there is a difference between Kolbs experiential learning model with the conventional model of learning to understand the basic competence - the base engine . In this study using experimental research designs is true experiment , because in this design the researcher controls all external variables that affect the experimental procedure used in this study is a pretest - posttest design types desaign control group . This research was conducted at SMK Negeri 1 Ampelgading . The population in this study was 5 class X class 2013/2014 . The samples used were 2 classes of class X TKR 1 number of 39 students of class X and TKR 4 number of 40 students . Class X TKR 1 as experimental class X and class 4 as a class kontrol.Penggumpulan TKR data using statistical and data analysis using the t test . Based on the analysis of data obtained that the average - average results of a study to understand the basic competence - basic engine in the experimental group were originally 51.20 into 82.82 or an increase of 71 % , whereas in the control group who initially had an average of 52 , 33 to 65.5 , or an increase of 29 % . calculation results of data analysis there is a difference between Kolbs experiential learning model with the conventional model of learning to understand the basic competence - the base engine . For teachers , the use of the application of Kolbs experiential learning can be one of the solutions and alternatives to improve student achievement.